2018
DOI: 10.2458/v25i1.22008
|View full text |Cite
|
Sign up to set email alerts
|

Testing the water, challenging the narratives of sustainable development: student volunteer research promoting public health in rural Panama in the shadow of an "eco-playground"

Abstract: This article describes challenges faced by a team of interns and students working for a not-for-profit sister company of a private U.S.-based land development company planning to build a "sustainable city" in the Panamanian forest. Testing the contaminated water of a nearby village, the team demonstrated that residents have been living with water-related illness. Despite the indifference and conflicting aims of the parent company, potentially impactful social capital connections were made. The author reflects … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 31 publications
0
3
0
Order By: Relevance
“…A study by Akoh and Lekhanya, [64] aiming to better understand the impact of networking challenges on social entrepreneurs and their contribution to long-term development concluded that networking issues continue to be a barrier to the value generation of social entrepreneurs. Alexander, [65] studied the difficulties encountered by a group of interns and students working for a non-profit sister firm of a private US-based property development company planning to establish a "sustainable city" in the Panamanian jungle. They explored the difficulties of the rural Panamanian people with contaminated drinking water and illnesses caused by it.…”
Section: Cluster 2: Climate Change and Sustainable Developmentmentioning
confidence: 99%
“…A study by Akoh and Lekhanya, [64] aiming to better understand the impact of networking challenges on social entrepreneurs and their contribution to long-term development concluded that networking issues continue to be a barrier to the value generation of social entrepreneurs. Alexander, [65] studied the difficulties encountered by a group of interns and students working for a non-profit sister firm of a private US-based property development company planning to establish a "sustainable city" in the Panamanian jungle. They explored the difficulties of the rural Panamanian people with contaminated drinking water and illnesses caused by it.…”
Section: Cluster 2: Climate Change and Sustainable Developmentmentioning
confidence: 99%
“…Topdown typically describes a neoliberal capitalist model of sustainability imposed from the outside. A common example is ecotourism focused on a convergence of environmental sustainability and economic sustainable development (Alexander 2018;Hill, Byrne and Pegas 2016). Even with an appreciation for environmental preservation, sustainable development as exemplified by corporate ecotourism models is still development based in "a top-down, ethnocentric, and technocratic approach, which treated people and cultures as abstract concepts" (Escobar 1995: 44).…”
Section: Ecotourism and Sustainability From The Bottom-up Or Top-downmentioning
confidence: 99%
“…However, stakeholders' underlying interpretations of the priorities that should govern sustainability diverge considerably, meaning that the term's polysemic nature entails tensions in practice. Public representations of congruence or commensurability between diverse interpretations of what sustainability is or should be entail considerable risks, explaining the need to analyze mediated narrative filters (Alexander 2018). This article posits that public representations of harmony between different stakeholders' understandings of 'sustainability' distract from and even perpetuate underlying inequalities and power asymmetries between global North and South, which matters given actors' resulting unequal ability to influence decision-making (Elgert 2012).…”
Section: Introductionmentioning
confidence: 99%